2016
DOI: 10.1055/s-0035-1561453
|View full text |Cite
|
Sign up to set email alerts
|

Maleimide-Modified Gold Nanoparticles (AuNPs): A Versatile ­Platform for Interfacial Click Reactions Leading to Chemically Modified AuNPs

Abstract: The maleimide moiety can undergo a wide variety of organic reactions, including Diels-Alder reactions, dipolar cycloadditions, and Michael-type additions, making it a suitable moiety for further elaboration of the functionality at the interface of gold nanoparticles (AuNPs) through key reactions that are useful in a host of applications. This account will cover: (1) our approach to prepare maleimide-AuNPs, (2) our survey of the scope of the reactivity of organic-solvent-soluble maleimide-AuNPs, which are very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The signals of hydrogen protons adjacent to difsulfide bond in (CPT) 2 ‐ss appeared at 2.83 and 4.02 ppm, while transferred to 3.08 and 4.41 ppm after reaction with 2,3‐dibromomaleimide (Figure S2d,e, Supporting Information). This change in chemical shift is caused by the electron‐withdrawing inductive effect of maleimide …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The signals of hydrogen protons adjacent to difsulfide bond in (CPT) 2 ‐ss appeared at 2.83 and 4.02 ppm, while transferred to 3.08 and 4.41 ppm after reaction with 2,3‐dibromomaleimide (Figure S2d,e, Supporting Information). This change in chemical shift is caused by the electron‐withdrawing inductive effect of maleimide …”
Section: Methodsmentioning
confidence: 99%
“…This change in chemical shift is caused by the electron-withdrawing inductive effect of maleimide. [25] The average size of DA-TAT-PECL micelles was 43.9 nm with low polydispersity index (PDI) of 0.135, indicating a narrow distribution of diameters ( Figure 1a). The transmission electron microscopy (TEM) image showed that the DA-TAT-PECL micelles exhibited a spherical shape and a nearly uniform distribution.…”
Section: Doi: 101002/adma201705436mentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, the interfacial chemistry between the two reaction moieties is orthogonal to the surface chemistry of the nanomaterial and leads to the desired (bio)conjugate with no effects on the nanomaterial stability. This approach to conjugation has demonstrated that nanomaterials can potentially be functionalized with any molecular system of interest through easy and reliable chemical reactions (Gobbo et al, ; Gobbo et al, ; Gobbo & Workentin, ; Gobbo et al, ).…”
Section: Introductionmentioning
confidence: 99%